واقع تكوين طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية بالمسيلة في ظل جائحة كورونا -دراسة ميدانية على طلبة التربية البدنية - خضراوي, خالد; طبوش, الطاهر; د.زاهوي, ناصر (My University, 2021)
الملخص: عنوان الدراسة: واقع تكوين طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية –جامعة مسيلة-في ظل جائحة كورونا (دراسة ميدانية على طلبة قسم التربية البدنية) أهداف الدراسة: - معرفة مدى تأثير الجائحة على التكوين والتحصيل الدراسي. - معرفة الجوانب المؤثرة في ميدان التكوين بمعهد علوم وتقنيات النشاطات البدنية والرياضية. - معرفة كيفية تأثير جائحة كورونا على التكوين ومحاولة إيجاد الحلول والاقتراحات المناسبة لاستمرارية التدريس سواء عن بعد أو التدريس الحضوري. مشكلة الدراسة: -ما واقع التكوين بمعهد علوم وتقنيات النشاطات البدنية والرياضية في ظل جائحة كورونا من وجهة نظر طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية تخصص تربية بدنية –جامعة المسيلة؟ فرضيات الدراسة: 1-هل هناك اتصال وتواصل بين طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية –جامعة المسيلة –وأساتذتهم في ظل جائحة كورونا؟ 2-هل هناك تحصيل علمي (أكاديمي) لطلبة معهد علوم وتقنيات النشاطات البدنية والرياضية –جامعة المسيلة –من خلال التعلم عن بعد في ظل جائحة كورونا؟ عينة الدراسة: هي عينة مسحية تتكون من 35 طالب من معهد علوم وتقنيات النشاطات البدنية والرياضية –جامعة مسيلة- قسم التربية البدنية. المنهج المتبع: المنهج الوصفي. أدوات الدراسة: الاستبيان. النتائج المتوصل إليها: - أن عينة الدراسة ومن خلال النتائج الخاصة بالفرضية الأولى والتي توضح الوصف الإحصائي لمدى وجود الاتصال والتواصل بين الطلبة والأساتذة وبالتالي لا توجد دلالة إحصائية للاختبارات ومنه لا توجد فروق ذات دلالة إحصائية بين المتوسط الحسابي والمتوسط الفرضي مما يدل على أن استجابة أفراد العينة تذهب في اتجاه الوسط الفرضي هذا ما يؤكد أن الفرضية الأولى (وبشكل متوسط) محققة. - هناك دلالة إحصائية للاختبارات ومنه هناك دلالة إحصائية بين المتوسط الحسابي والمتوسط الفرضي وعند المقارنة بينهما نجد أن الفروق لصالح المتوسط الفرضي (قيمة الاختبار سالبة) مما يدل على أن استجابات أفراد العينة تذهب في الاتجاه السلبي هذا ما يؤكد أن الفرضية الثانية غير محققة Summary of the study: Title of the study: The fact that students from the Institute of Physical and Mathematical Sciences and Techniques are formed under the Corona pandemic (field study for students from the Department of Physical Education) Objectives of the study: - To know the impact of the pandemic on education and achievement. - Knowledge of relevant aspects of training at the Institute of Physical and Mathematical Sciences and Techniques; - To find out how the Corona pandemic affects training and to try to find appropriate solutions and proposals for the continuity of distance and in-attendance teaching. Study problem: What is the reality of training at the Institute of Physical and Mathematical Science and Technology under the Corona Pandemic from the point of view of the students of the Institute of Physical and Mathematical Science and Technology, which specializes in physical-physical education? Hypotheses of the study: Are there any contacts and contacts between students of the Institute of Physical and Mathematical Science and Technology - the Liquor Society - and their families under the Corona pandemic? Is there an academic achievement of students from the Institute of Physical and Mathematical Science and Technology through distance learning in the Corona pandemic? Sample study: It is a survey sample consisting of 35 students from the Institute of Physical and Mathematical Activities Science and Techniques, the Department of Physical Education. Approach: Descriptive approach. Study tools: Questionnaire. Findings: - The study sample and the results of the first hypothesis, which show the statistical description of the extent of communication and communication between students and professors and therefore no statistical significance of the tests, and hence no statistically significant differences between the arithmetic and the hypothetical mean indicating that the response of the sample members goes in the direction of the hypothetical medium, confirms that the first hypothesis (and mediocre) is realized. - There is a statistical significance to the tests and there is a statistical significance between the arithmetic average and the hypothetical mean. When compared, the differences in favour of the hypothetical mean (negative test value) indicate that the responses of the sample members go in the negative direction. This confirms that the second hypothesis is not realized.
Keywords: تكوين الطلبة; معهد علوم وتقنيات النشاطات البدنية والرياضية; جائحة كورونا